Biodegradation of ZEN by Bacillus mojavensis L-4: analysis of degradation conditions, products, degrading enzymes, and whole-genome sequencing, and its application in semi-solid-state fermentation of contaminated cornmeal - Chang, Jiagao; Dong, Wenxuan; Gao, Shansong; Hou, Lele; Dong, Jihong; Qiu, Huiling; Chen, Fu (Frontiers in Microbiology, 2025)
Zearalenone (ZEN), a naturally occurring estrogenic mycotoxin prevalent in cereals and animal feed, poses significant challenge to livestock industry owing to its detrimental effects on animal reproduction. In this study, the strains with high degradation rate were screened through co-culture with ZEN, and identified by bacterial morphology, 16S rDNA sequencing and whole genome sequencing. The detoxification effect of L-4 strain on ZEN was evaluated under different ZEN concentration, treatment time, pH value and temperature, the degradation products were identified, and the degradation effect of L-4 strain on ZEN contaminated corn meal was evaluated. The ZEN degrading enzyme sequence was obtained through the whole genome protein sequence analysis of strain L-4, and the ZEN degrading enzyme was verified by molecular binding and addition of catalase. We isolated Bacillus mojavensis L-4 from the cecal content of laying hens, which demonstrated exceptional ZEN-degrading efficiency. Under optimized conditions (pH 7.0, 37 °C), L-4 completely degraded 0.5–1.0 μg/mL ZEN into less toxic 15-OH-ZEN within 24 h. Importantly, L-4 achieved a 49.41% degradation rate for ZEN in cornmeal. Whole-genome sequencing of L-4 revealed the presence of ZEN-degrading genes and enzymes. In particular, efeB 3668, a peroxidase-like enzyme with high homology (95.91%) to BsDyP from Bacillus subtilis, played a key role in ZEN detoxification primarily through hydrogen bonding and hydrophobic interactions. Thus, the rapid and effective degradation of ZEN by B. mojavensis L-4, coupled with its adaptability to diverse environments, underscores its potential application in safeguarding animal health and mitigating environmental pollution.